Amos Decker : The Fix - Book 3 - Baldacci, David; Brewer, Kyf.; Cassidy, Orlagh; Hachette Audio (Firm) ([New York] : Hachette Audio, 2017)
Following his number one New York Times bestsellers Memory Man and The Last Mile, David Baldacci returns with his next thriller featuring detective Amos Decker.
Keywords: Decker, Peter (Fictitious character) -- Fiction; Murder -- Fiction -- Investigation; Audiobooks; Thrillers (Fiction); Audiobooks; Audiobooks